Queen polymorphism in Acanthomyrmex careoscrobis Moffett, 1986 in Peninsular Malaysia (Hymenoptera: Formicidae: Myrmicinae), with descriptions of hitherto unknown female castes and males - Yamada, Aiki; Ito, Fuminori; Hashim, Rosli; Eguchi, Katsuyuki (Penerbit Universiti Malaysia Sabah, 2018)
The present study presents biological observations on colony characteristics of Acanthomyrmex careoscrobis Moffett, 1986 in Ulu Gombak (Selangor, Malaysia), with redescription of the minor worker and descriptions of the hitherto unknown female castes and males. The colony of A. careoscrobis can produce both alate and ergatoid queens. Ergatoid queens may function as cheap secondary reproductive females, whereas it is at present unclear whether they engage in dependent colony foundation or not. Ergatoid queens have the same number of ovarioles as alate queens, and show variable intermediate external morphology between major workers and alate queens. The colony redistributes nutrients via trophic eggs among colony members. Reviewing current available data for other Acanthomyrmex species, this study highlights the great prevalence and diversity of ergatoid queens in this poorly-studied genus.